The Polymorphism of Insulin-Like Growth Factor-1 Receptor Gene and Its Associations with Live Weight Traits and Birth Type in Akkaraman Lambs - Yüksel, Merve; Bayram, Davut; Arslan, Korhan; Daldaban, Fadime; Çınar, Mehmet Ulaş; Akyüz, Bilal (My University, 2024)
The insulin-like growth factor 1 receptor (IGF1R) gene is a potential candidate gene as it is involved in several physiological processes related to yield charecteristics. We conducted this study to investigate a polymorphism (g.195C>T) in the IGF1R gene, identified using the Rsal enzyme, and its associations with live weight gain from birth to weaning and birth type in the Akkaraman sheep breed. A total of 397 male Akkaraman breed lambs were examined. The samples analyzed have revealed three distinct genotypes (AA, AB, BB) in terms of the g.195C>T polymorphism as a result of the utilized polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). As a result of Chi-square analysis using genotypic data, it was determined that the examined samples were not in Hardy-Weinberg equilibrium for IGF1R-Rsal polymorphism. Throughout the growth period from birth to 90 days, slight differences in growth rates were observed due to the effects of birth type and IGF1R genotypes. However, these differences were not statistically significant across genotypes in terms of live weight gain. Additionally, it was observed that the BB genotype had a higher frequency in single-born lambs, and there was a statistically significant relationship between IGF1R-Rsal polymorphism and lamb birth type (p<0.01). The results have considered that it was necessary to suggest that new studies might be planned to investigate the relationship between IGF1R-Rsal polymorphism and other yield characteristics, especially birth type, in sheep
Keywords: Genetik ve Kalıtım